Rule of Law for Nature : New Dimensions and Ideas in Environmental Law - Voigt, Christina (Cambridge : Cambridge University Press, 2013)
'Human laws must be reformulated to keep human activities in harmony with the unchanging and universal laws of nature.' This 1987 statement by the World Commission on Environment and Development has never been more relevant and urgent than it is today. Despite the many legal responses to various environmental problems, more greenhouse gases than ever before are being released into the atmosphere, biological diversity is rapidly declining and fish stocks in the oceans are dwindling. This book challenges the doctrinal construction of environmental law and presents an innovative legal approach to ecological sustainability: a rule of law for nature which guides and transcends ordinary written laws and extends fundamental principles of respect, integrity and legal security to the non-human world.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Environmental law, International; Environmental protection; Rule of law